Incidence of postoperative delirium according to cognitive status, improved responsiveness and inflammatory response at elderly patients in urgent abdominal surgery - Demyter, I.; Gudz, D.; Vorotyntsev, S.; Демитер, І.; Гудзь, Д.; Воротинцев, Сергій Іванович (My University, 2019)
Background. Postoperative delirium (POD) is a clinical syndrome that is manifested in impaired consciousness and attention, perception, memory, thinking and psychomotor behavior after surgery. Me thods . After passing the Bioethics Commission at Zaporizhzhya State Medical University and obtaining informed consent from patients, 30 elderly patients who underwent surgical interventions on the abdominal organs under urgent procedure were sequentially included in a single-center prospective study. Patients with a history of traumatic brain injury or stroke with neurological impairments in the form of sensory-motor aphasia and plegia were excluded from the study. Re sul t s .The study involved 30 patients (16 (53%) women and 14 (47%) men), aged 62 years to 92 years, grade III-IV ASA, who underwent urgent surgery for bowel tumors (n = 8), gallstone disease (n = 7), entrained inguinal and postoperative ventral hernias (n = 10), gastric or intestinal perforation (n = 5). Postoperative delirium occurred in 33% of patients. On the first day after surgery, the cognitive status of patients in the first group decreased by 1 point relative to the primary assessment (p = 0.88), when on the second postoperative day the indicator returned to baseline. Patients in the second group showed a sharp impairment of cognitive abilities in the postoperative period, associated with POD and a significant decrease in cognitive status at day 5 (p <0.05) compared with preoperative assessment. The level of inflammatory response of the body in the preoperative period is 1.5 times higher in patients with POD (p = 0.01). The correlation between leukocytosis level and POD revealed a moderately significant relationship between these indicators (rs = 0.45 at p <0.05). Conclusions. In 33% of urgent patients, abdominal surgery revealed postoperative delirium, which is reliably dependent on cognitive deficits for surgery and the level of systemic inflammation (p = 0.01). The level of patient wear does not significantly affect the incidence of POD.
Keywords: elderly patient; postoperative delirium; cognitive status; urgent abdominal surgery